ROLE OF PHYSICAL DEVELOPMENT PARAMETERS IN DETERMINATION OF AGE OF JUVENILES: A RESEARCH STUDY (Journal of Forensic Medicine & Toxicology, 2014)
The present study relates to study of role of physical development of juveniles mainly the appearance of secondary sexual characters in the age group 12 -20 years. While determining the age of juvenile in conflict with law as one of the three criteria for estimation of the age. The study covers the period of last 6 years 2007 – 2012 and has tried to evolve the physical development parameters for the mixed population of Delhi.
Keywords: Juvenile; Age estimation; Secondary sexual characters; Juvenile Justice (Care and Protection of Children) Act,3rd molar; parameters